MON-653 The Effects of DPP IV Inhibitor on Glycemic Variability in Type 2 Diabetic Patients Treated with Twice Daily Premixed Human Insulin - Tan, Florence Hui Sieng (J Endocr Soc, 2020)
Glycemic variability (GV) is emerging as an exciting therapeutic target for diabetes mellitus (DM) with recent evidences showing association of GV with hypoglycemia risk as well as chronic complications.(1,2) Twice daily human premixed insulin is commonly used in developing countries and Asia for treatment of type 2 DM (T2DM). (3) While more convenient and cost saving, human premixed insulin regime may increase GV due to lesser flexibility and less physiological pharmacokinetic profile. Dipeptidyl peptidase IV inhibitors (DPPIV-I) have been shown to improve GV when used for treatment of T2DM but the effects of DPPIV-I when added on human premixed insulin is limited. We therefore evaluated the changes in GV following addition of DPP IV-I among T2DM patients treated with premixed human insulin with or without metformin therapy. This was a prospective study involving adult patients with T2DM on stable doses of premixed human insulin with or without metformin for at least 3 months from two state hospitals in Malaysia. Blinded continuous glucose monitoring (CGM) were performed at baseline and following 6 weeks of adding Vildagliptin to their insulin regime. A total of 12 patients were recruited (50% male). Mean (SD) age was 55.8 (13) years with mean duration of disease of 14 (6.6) years. The addition of Vildagliptin significantly reduced GV indexes including SD 2.98 (1.17) to 2.33 (0.82), p=0.017; MAGE 6.94 (2.61) to 5.72 (1.87), p=0.018; MAG 1.60 (0.76) to 1.23 (0.48), p=0.009 and M Value 13.96 (13.01) to 6.52 (7.45), p=0.037. In addition there were improvements in terms of parameters for glycemic control. Time spent in optimal glycemic range (4-8 mmol/l) improved from 38.33 (19.69) to 58.17 (5.95) %, p=0.001 with reduction in AUC for hyperglycemia from 2.09 (1.73) to 1.06 (1.09) mmol/day, p=0.010. Hypoglycemia events were infrequent and the reduction in time spent in hypoglycemia [5.92(9.74) to 1.91 (2.54)%, p=0.191] as well as AUC for hypoglycemia [0.03(0.54) to 0.01(0.02) mmol/day, p=0.163] were found although these did not reach statistical significance. We concluded that addition of DPP IV-I to commonly prescribed twice daily premixed human insulin regime in patients with T2DM may improve GV and glycemic control and warrant further exploration. References (1) Gerry Rayman. Glycaemic control, glucose variability and the triangle of diabetes care. Br J Diabetes 2016;16(Suppl1):S3-S6 (2) Boris P. Kovatchev. Metrics for glycaemic control - from HbA1c to continuous glucose monitoring. Nat Rev Endocrinol. 2017 Jul;13(7):425-436 (3) Kalra S, Balhara YP, Sahay BK, Ganapathy B, Das AK. Why is premixed insulin the preferred insulin? Novel answers to a decade-old question. J Assoc Physicians India. 2013 Jan;61(1 Suppl):9-11